Analisis Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan pada Counter Handhphone â€œVenus Cellularâ€ Tangerang - Dewi, Risfa; Suseno, Andri; Adhi, Mertha Widiyastuti (Ridwan Institute, 2021)
The purpose of this study was to analyze the Effect of Product Quality on Customer Satisfaction on Handhphone Counter